The Influence of Return on Equity Ratio and Debt to Equity Ratio to Price to Earning Ratio in Galvalum Companies Listed on the Indonesia Stock Exchange for the 2014-2018 Period - Hendro Waryanto (PINISI Discretion Review, 2019)
The development of the capital market in Indonesia has encouraged companies to sell their shares to the public so that more companies are listed on the Indonesian stock exchange. This study aims to determine the effect of Return On Equity Ratio and Debt to Equity Ratio on Price to Earning Ratio in Galvalum Companies listed on the Indonesia Stock Exchange Period 2014-2018. The method used is explanatory research with a sample of 5 years of financial statements. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study Return On Equity Ratio significantly influence the Price to Earning Ratio of 47.8%, the hypothesis test obtained significance of 0,000 <0.05. Debt to Equity Ratio has no significant effect on Price to Earning Ratio of 0.01%, the hypothesis test obtained significance of 0.900> 0.05. Return On Equity Ratio and Debt to Equity Ratio simultaneously have a significant effect on Price to Earning Ratio of 49.2%, hypothesis testing obtained significance of 0,000 <0.05.